Assessment of luteolin (3',4',5,7-tetrahydroxyflavone) neuropharmacological activity - Coleta, Miguel (2008)
Since the discovery that certain flavonoids (namely flavones) specifically recognise the central BDZ receptors, several efforts have been made to identify naturally occurring GABAA receptor benzodiazepine binding site ligands. Flavonoid derivatives with a flavone-like structure such as apigenin, chrysin and wogonin have been reported for their anxiolytic-like activity in different animal models of anxiety. Luteolin (3',4',5,7-tetrahydroxyflavone) is a widespread flavonoid aglycon that was reported as devoid of specific affinity for benzodiazepine receptor (BDZ-R) binding site, but its psychopharmacological activity is presently unknown. Considering (1) the close structural similarity with other active flavones, (2) the activity of some of its glycosilated derivatives and (3) the complexity of flavonoid effects in the central nervous system, luteolin was submitted to a battery of tests designed to evaluate its possible activity upon the CNS and its ability to interact with the BDZ-receptor binding sites was also analysed.